Reform of agricultural markets in India: A critical analysis - Narayanan, Sudha (2022)
Why is agricultural marketing so crucial for the farmer? Agriculture and allied sectors accounted for only 17.7 per cent of the GDP of India in 2020. Yet, as much as 54.6 per cent of India’s workforce, as per the Census of 2011, relied on this sector for employment and incomes. Although agricultural households earned incomes from several sources, a major portion was still earned from agriculture and allied activities. As per the 2013 Situation Assessment Survey of Agricultural Households (SAS), agricultural households earned 48 per cent of their income from crop cultivation, 12 per cent of their income from animal husbandry and 32 per cent of their income from wages.